Intra-Host Diversity of Dengue Virus in Mosquito Vectors - Bifani, Amanda Makha; Siriphanitchakorn, Tanamas; Choy, Milly M. (Frontiers in Cellular and Infection Microbiology, 2022)
Dengue virus (DENV) is the most common arbovirus, causing a significant burden on both the economy and global healthcare systems. The virus is transmitted by Aedes species of mosquitoes as a swarm of closely related virus genomes, collectively referred to as a quasispecies. The level of genomic diversity within this quasispecies varies as DENV moves through various ecological niches within its transmission cycle. Here, the factors that influence the level of DENV quasispecies diversity during the course of infection in the mosquito vectors are reviewed.